Peningkatan Kapasitas Meliponikultur dengan Pengayaan Pakan Lebah Madu di Kelurahan Kahu Kecamatan Bontocani Kabupaten Bone - Sitti Nuraeni; Budiaman Budiaman; Andi Sadapotto; Baharuddin Baharuddin; Marwan Rajab; Andi Prastiyo (Universitas Mataram, 2021)
The purpose of this community service program is to provide knowledge about the importance of forests, woody forage plants and enrichment of feed types around meliponiculture farmer groups. The methods used in this activity as part of the mentoring are pre-tests, lectures, video screenings, discussions about knowledge of forest bee hunting, trigona beekeeping and the importance of forests and bee feed. The next activity was the distribution of flowering tree seedlings and visits to the meliponiculture location for farmer groups. The result of this community service activity is that the community in Kahu Village can develop knowledge about the material presented by seeing the enthusiasm and appreciation of the participants or members of the farmer groups who participated in the many questions during the discussion. Receipt of plant and tree seeds that are distributed immediately to the plant and group reception during visits to their meliponiculture area. Awareness of planting various types of vegetation and maintaining forests is an important factor for the stability of colony strength and can even increase the beekeeping productivity of all types of bees in Kahu Village, Bontocani District and its surroundings. Assistance from various parties is needed in order to increase the productivity of honey bee cultivation in Kahu Village, Bontocani District.